DERRICK CRANE ROBUSTNESS SCENARIOS - Bernuzzi, Claudio; Bertinotti, Elisa; Frau, Massimo; Simoncelli, Marco (Journal of Applied Engineering Science, 2022)
The paper deals with derrick cranes (derricks), that are equipment typically used in mining industry and the focus is the analysis of few robustness scenarios. Derricks are composed by built-up steel members, which are widely and efficiently used in hoisting applications, due to theirs high payloads at relevant outreaches. As during the in-service use local damages might occur, aim of the paper is to study how such damages should influence the overall structural performance. In particular, reference has been made to a derrick for which six geometrical configurations and five different damage scenarios have been analyzed. Owing to the extensive use of angles in the built-up component of each derrick, structural analyses have been carried out by using a commercial refined finite element analysis package (FEAP) offering the warping torsion as additional degree of freedom for each beam node. Research outcomes allow for a clear identify the parts of derrick which should be protected and well-designed to guarantee a robust structure for the total in-service life.
Keywords: derrick crane, steel angle, warping torsion, robustness analysis , localized damag